World Englishes: Changing the Paradigm of Linguistic Diversity in Global Academia - Azizah Alogali (Research in Social Sciences and Technology, 2018)
This paper discusses the ways that the publications of multilingual and non-native speakers of English are treated in academic publications. Using the World Englishes theory as a framework, it attempts to enumerate which overt and hidden advantages native speakers may have over non-native speakers in academic writing communities, and how these can be deconstructed. It also explores possible solutions to this problem, both to improve non-native students' written scholarly work and to restructure global perceptions and biases towards different regional varieties of English. The paper focuses on certain gatekeeping behaviors performed by institutions of knowledge production, and on how the World Englishes theory can be applied to help improve parity in international academia.